Inclusion of waste pickers in the reverse logistics of Waste Electrical and Electronic Equipment (WEEE) – the case study of Projeto Eco Eletro - Ferreira, Vivian Fernandes Marinho; Gonçalves-Dias, Sylmara Lopes Francelino; Vallin, Isabella de Carvalho (Desenvolvimento e Meio Ambiente, 2019)
This paper aims to understand the insertion of cooperatives of recyclable waste pickers in the market of Waste Electrical and Electronic Equipment (WEEE) in Brazil based on the National Policy on Solid Waste (PNRS). To that end, a case study of the Projeto Eco Eletro was undertaken. The policy is first described in general terms and then explored in specific topics. Six interviews with different actors in the field of electronics were also carried out. The main results were the summarization of four critical points present in the PNRS for the inclusion of waste pickers into the WEEE market, and opportunities and challenges faced by the Projeto Eco Eletro, which are the same as those faced by cooperatives in their day-to-day work within the WEEE market. It was concluded that there is a clear barrier in the access of the waste pickers’ cooperatives in sectoral negotiations and in the market. Furthermore, there is a contradiction by the government, which envisioned the inclusion of collectors without promoting concrete actions for such inclusion to occur, especially given the existent economic interests in the sector.